Penerapan Praktik Community Volunteering Melalui Kebijakan Employee Voluntary Hour Dalam Pelaksanaan Program CSR Pt. Karakatau Posco : (Studi Kasus Program Sekolah Binaan Di Kecamatan Citangkil dan Ciwandan, Kota Cilegon, Banten) - Yuliantini, Nur Fajria; Fitriyah, Fitriyah (Jurnal Ilmu Kesejahteraan Sosial, 2016)
This study discusses application of practice community volunteering through policy employee voluntary hour in implementation CSR program PT. Krakatau Posco (case study of school patronage program in district Citangkil and Ciwandan, Cilegon City, Banten). Descriptive qualitative was used in this study. The technique of informant selection in this study was used purposive sampling. The study shows corporate interpretation of a kind CSR implementation that is community volunteering through employee voluntary hour’s policy. Although in context of Indonesia’s CSR implementation, PT. Krakatau Posco having character of discretionary. But, through employee voluntary hour that is obligation for company’s employees to carry out sosial activitywith provisions 23 social hours/ 1 year in neighborhood community make CSR implementation from discreationary to necessity. However in implementation, this practice having some lacked but also can give motivation for employee to doing social activity and impact of positive for beneficiary school. Community volunteering is a kind of CSR implementation which rare in others Indonesia’s companies. Because need riped preparation and through employee voluntary hour’s policy, PT. Krakatau Posco try represent other shape of this practice.